2018
DOI: 10.20429/stem.2018.020105
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Integrating LEGO Robotics Into a Mathematics Curriculum to Promote the Development of Proportional Reasoning

Abstract: A mixed methods, action research case study was conducted to investigate the effects of incorporating LEGO robotics into a seventh-grade mathematics curriculum focused on the development of proportional reasoning through the lens of Social Constructivist Theory. This study applied students' prior knowledge of the distance, rate, and time formula as they used LEGO EV3 robots to calculate the rate of a robot. The information gained was applied to different iterations, and structures, of the formula to support th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Sullivan and Heffernan (2016) found that robotics construction kits (RCKs), such as Lego Mindstorms EV3 robots, provide immediate feedback to learners that promote learning through reflection and discussion. Furthermore, the authors found that P-12 students progressed through problem-solving cycles while learning with the RCKs, which is supported with the findings from research on proportional reasoning (Casler-Failing 2018a, 2018b, in which middle-grades students progressed through the five stages of technology integration -engagement, exploration, investigation, creation and evaluation (Carbonaro, Rex, and Chambers 2004) Whether the student partaking in the learning is a PST or a middle-grades student, 'the value of the technology depends on whether students actually engage with specific technologies or tools in ways that promote mathematical reasoning and sense making' (NCTM 2014, p. 80). PSTs must possess sufficient TK, in parallel with their CK and PK, in order to appropriately meet the needs of their diverse learners.…”
Section: Learning About Roboticssupporting
confidence: 63%
See 1 more Smart Citation
“…Sullivan and Heffernan (2016) found that robotics construction kits (RCKs), such as Lego Mindstorms EV3 robots, provide immediate feedback to learners that promote learning through reflection and discussion. Furthermore, the authors found that P-12 students progressed through problem-solving cycles while learning with the RCKs, which is supported with the findings from research on proportional reasoning (Casler-Failing 2018a, 2018b, in which middle-grades students progressed through the five stages of technology integration -engagement, exploration, investigation, creation and evaluation (Carbonaro, Rex, and Chambers 2004) Whether the student partaking in the learning is a PST or a middle-grades student, 'the value of the technology depends on whether students actually engage with specific technologies or tools in ways that promote mathematical reasoning and sense making' (NCTM 2014, p. 80). PSTs must possess sufficient TK, in parallel with their CK and PK, in order to appropriately meet the needs of their diverse learners.…”
Section: Learning About Roboticssupporting
confidence: 63%
“…When an individual possesses TPACK in regard to robotics, I suggest they are able to make sound pedagogical decisions on when, and how, to use robotics to teach or apply mathematical concepts. For example, choosing to use robotics to predict, measure and evaluate the accurateness of a proportional relationship as opposed to showing a video or using a whiteboard would not only create engagement in the activity but also allow students to see and experience the reasonableness of their mathematical work (Casler-Failing 2018b).…”
mentioning
confidence: 99%